PEMANFAATAN CITRA QUICKBIRD UNTUK PEMETAAN JALAN ALTERNATIF KEMACETAN LALU LINTAS DI SEBAGIAN KOTA SEMARANG (Studi Kasus : Jalan Arteri Kota Semarang Bagian Selatan) - , WIDYA ANGGRAINI L; , Drs. Zuharnen, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Population growth impact urban development that is to be supported with changes in land use and transportation development. Transportation development supported by utulities (the movement of people and traffic) and the infrastructure of roads. Quickbird image the scale of detail to provide information variation object to median that it can be used in urban studies, such as the study of traffic. Traffic management that can be done through Geographic Information System technology in the form of recommendations to alternative road. Arterial road of Semarang city the southern used as traffic-lane city/ district, inter-city where often occurs value added number of vehicles at a particular time and resulted in traffic jam, characterized by a decrease in LOS, so the need of recommendation the alternative roads as one of the options solve the problem of traffic jam. The purposes of this study are (1) knowing distribution current condition of traffic jam arterial road of Semarang city southern. Current conditions as of barrier by network analyst resulted in alternative road recommendation (2). The method of this study are method of marger Remote Sensing technique and Geographic Information System technology accompanied by field data and secondary data. Remote sensing techniques are used for the interpretation of image Quickbird in the form of lanuse and geometric roads. The technique of Geographic Information System for processing and analysis of field data to produce spatial and nonspatial. Data of field survey (the calculation of vehicles, capacity and quality of roads) to inform the traffic volume and road capacity, which resulted in LOS and DSratio. The result of this study are knowing the distribution conditions of traffic jams that it can identify the traffic management are the recommendation of alternative road are route nearest of the location of the start to finish. The management that considers the current conditions and DSratio so it formed category management where the road is passed or avoided. Alternative roads prevent the traffic jams focus to the user of motorcycles and light vehicle. This category applied in network analyst who considering Shortest of the distance traveled and at least be intersection to be accommodated with the results of the mapping of alternative roads.